Strategi Tata Kelola Perpustakaan Di Pondok Pesantren Mawaridussalam Batang Kuis Deli Serdang - Retno Sayekti, Yusra Dewi Siregar, Rizkon Jadidah Pasaribu (Pusdikra Publishing, 2022)
This research aims to review the governance strategy of Mawaridussalam Islamic boarding school library. This research aims to find out how planning strategy, organizing strategy, briefing/mobilization strategy, and library governance supervision strategy in Mawaridussalam Islamic boarding school Batang Kuis Deli Serdang. This research uses a qualitative approach, where data is collected through methods: interviews and documentation studies. Data analysis techniques are carried out with three paths, namely: data presentation, data reduction, and conclusion drawing. The results of this study show that the library governance strategy in Mawaridussalam Islamic boarding school has been implemented optimally following the national standards of the library although there are still some management procedures whose implementation is still not fully followed.